2011
DOI: 10.1186/1743-422x-8-169
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of persistent infection with foot-and-mouth disease virus in BHK-21 cells

Abstract: BackgroundFoot-and-mouth disease virus (FMDV) is able to cause persistent infection in ruminants besides acute infection and disease. Since the mechanisms of viral persistence and the determining factors are still unknown, in vitro systems help explore and reveal mechanisms of persistence in vivo by providing useful models for the study of RNA genome mutations and evolution. Ammonium chloride, a lysosomotropic agent that raises intralysosomal pH, reduces the yield of FMDV during infection of BHK-21 cells.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 33 publications
6
30
0
Order By: Relevance
“…This is in concurrence with earlier observation that FMDV particles locate into endosomes in the cytoplasm of infected BHK-Op48 cells (Huang et al, 2011). Taken together, our data demonstrate that expression of precursor polypeptide and mutant 3C in a single frame resulted in the production of structural proteins that self assembled into empty FMDVlike particles.…”
Section: Discussionsupporting
confidence: 93%
“…This is in concurrence with earlier observation that FMDV particles locate into endosomes in the cytoplasm of infected BHK-Op48 cells (Huang et al, 2011). Taken together, our data demonstrate that expression of precursor polypeptide and mutant 3C in a single frame resulted in the production of structural proteins that self assembled into empty FMDVlike particles.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the expression of viral antigens in these cells depended on cell density and increased with cell confluence. As described in other studies, no CPE was observed from passage 1 to 42, comparing persistently infected cultures with the corresponding uninfected cultures [25,40].…”
Section: Discussionmentioning
confidence: 53%
“…Recently, another model was established using FMDV serotype O and BHK-21 cells treated with ammonium chloride. [25]. Functional genomics studies in these persistently infected BHK-21 cells compared with acutely and mock-infected cells showed differences in 12 cellular gene expression patterns [53].…”
Section: Introductionmentioning
confidence: 97%
“…144.0 /animal), draught energy wastage average 12.48 kilo watt hr/animal, and land left uncultivated average .72/ animal (Rahman et al, 1985). A lot of epidemiological and molecular research works have been conducted on FMD virus but in clinical aspects has few studied in Bangladesh (Islam et al, 2000;Howlader et al, 2004;Sarker et al, 2011;Hossen et al, 2014;Rahman et al, 2015) and in the world (Edwards, 2004;Durand et al, 2008;Fernandez et al, 2008;Ryan et al, 2008;Huang et al, 2011). There is no published data so far on prevalence of FMD in Gazipur district of Bangladesh although this region has huge number of livestock population.…”
Section: Introductionmentioning
confidence: 99%